Detection of microplastics in the feline placenta and fetus - Ilaria Ferraboschi; Francesca Canzolino; Elena Ferrari; Cristina Sissa; Matteo Masino; Matteo Rizzi; Simona Bussolati; Giuseppina Basini; Simone Bertini; Stefano Grolli; Roberto Ramoni; Francesco Di Ianni; et al. (PLoS ONE, 2025)
The present study aimed to detect microplastics in feline placentas and fetuses in the early stage of pregnancy. For this study, 8 pregnant queens were evaluated. A standardized protocol for the digestion of biological matter was used, as well as a plastic-free approach for sample collection and manipulation. Microplastics were investigated by means of Raman spectroscopy, with the aim of identifying their composition. Four of eight animals were contaminated, with a total of 19 microplastics detected in both fetal and placental samples. Specifically, fetuses from cats 4 and 7 were contaminated, as were the placentas from cats 5, 6, and 7. This work demonstrates that microplastics can accumulate in feline placentas even at the early stage of pregnancy. Moreover, preliminary results of the presence of microplastics in feline fetuses are shown, suggesting that microplastics can cross the placental barrier.